Effects of COVID-19 on Trade, Industrialisation and Globalisation in Africa. (2021)
This paper examined the potential effects of the global Corona Virus (COVID-19) pandemic on the paths of international trade, industrial development and economic globalization on the African continent. Deploying a purely descriptive analytical approach, a number of submissions are made. One, the pandemic significantly disrupted African trade -on both import and export sides - particularly owing to the closures of ports and other external trade infrastructure in China which is the largest trading partner for most African countries. Two, and somewhat related to the first point, the manufacturing sector that is meant to propel industrialization on the continent was also hard hit especially due to the huge shock to the supply chains of intermediate inputs. Third, since globalizations -on both the economic and cultural fronts- has led to greater interconnectedness, spillovers of the negative shock from China to other parts of the world including Africa is more palpable than otherwise. On the basis of the foregoing, some propositions on the key efforts that should be pursued and intensified are highlighted.